Training effectiveness: the role of training design, training participants’ characteristics, work environment, motivation to transfer, and organizational learning culture / Saiful Anuar Alias - Alias, Saiful Anuar (2019)
Training serves a key role for both public and private sectors in enhancing the knowledge, skills, and attitudes of employees within an organization. Expectedly, the training for the development of human resource contributes an added competitive advantage to the organization in delivering quality products and services. Addressing that, this study assessed the training effectiveness of leadership and management training programme at National Institute of Public Administration (INTAN) for Malaysian civil service employees in terms of their characteristics, work environment, and the training design. The model of training effectiveness by Saks and Haccoun (2007) and the four-level training evaluation model of Kirkpatrick (1996) established the underlying basis of this study. Using the mixed-methods approach, this study quantitatively assessed the relationships of training design, training participants‘ characteristics, and work environment with training effectiveness of Level 1 in terms of trainee‘s reaction. Furthermore, this study also assessed the extent of learning with respect to the evaluation of Level 2 (learning performance) based on the outcomes of pre-test and post-test. This study subsequently applied the qualitative approach to explore the transfer of learning (Level 3) at the workplace among the training participants after completed the training. Overall, the relationships of training design and work environment of training participants with training effectiveness were found significant. However, the training participants‘ characteristics exhibited not significant effect towards training effectiveness. Motivation to transfer was found fully mediated the relationship between training participants‘ characteristics and training effectiveness. In addition, the organizational learning culture was found to moderate the positive relationship between work environments and training effectiveness. This study further revealed that the training participants experienced effective learning and obtained adequate opportunities to apply the training content at the workplace. The findings of this study highlighted the significant roles of training provider and training practitioners in designing effective training programmes to provide rich learning experience for effective transfer of learning at the workplace. It is also imperative that the organizations cultivate continuous learning culture to promote knowledge-sharing and transfer of learning within the organization.